P96 THE CURRENT ROLE OF ADJUVANT THERAPY IN PATIENTS FOLLOWING NEO-ADJUVANT CHEMOTHERAPY AND R0 RESECTION FOR LOWER OESOPHAGEAL AND GOJ ADENOCARCINOMA. (23rd November 2019) - Bott, R; Zylstra, J; Wilkinson, M; Knight, W; Baker, C; Kelly, M; Maisey, N; Beckmann, K; Van, Hemelrijck M; Gossage, J; Allum, W; Smyth, E; et al.
Abstract: Aim:  The aim of this study was to assess the survival benefit of adjuvant therapy in R0 resection patients following neo-adjuvant chemotherapy and surgery for lower oesophageal and GOJ adenocarcinoma. Background & Methods:  The role of adjuvant therapy in oesophago-gastric adenocarcinoma patients treated by neo-adjuvant chemotherapy is contentious. In UK practice surgical resection margin status is often used to stratify patients into receiving adjuvant treatment. Two prospectively collected institutional databases were combined. Patients were classified by the adjuvant therapy received. Crude and adjusted Cox regression analyses compared overall and recurrence free survival according to the adjuvant treatment, stratified by resection margin status. Recurrence patterns were assessed as a secondary outcome. Results:  A total of 616 patients were included (373 R0, 243 R1). In hospital mortality following surgery was 1% and these patients were excluded from analysis (n=7). In the R0 resection group 220 patients (59%) had no adjuvant treatment and 137 patients (37%) had adjuvant chemotherapy. On adjusted analysis pathological N status (p<0.0001), poor differentiation (p=0.005) and poor response to neo-adjuvant chemotherapy (p=0.001) were independently associated with poor survival. The benefit of adjuvant chemotherapy did not reach independent significance (HR 0.65 95% CI 0.40-1.06; p=0.087) compared to no treatment. However, it was observed that responders to neo-adjuvant chemotherapy (Mandard 1-3) were more likely to demonstrate a survival benefit from adjuvant chemotherapy (HR 0.42 95%CI 0.15-1.11; p=0.081) than those who are deemed to be non-responders (Mandard 4&5, HR 0.71 95%CI 0.39-1.32; p= 0.280). Conclusion:  Adjuvant chemotherapy may have a survival benefit in R0 resection patients following surgery, but this is likely to be limited to patients exhibiting a good response to neo-adjuvant chemotherapy.